Latex, preparation method thereof and electrochemical device
By preparing core-shell structure latex as adhesive, the problem of decreasing bonding force caused by the reduction of adhesive in lithium/sodium-based battery electrode sheet is solved, high energy density and stability at low usage is achieved, and the cycle life of the battery is improved.
Patent Information
- Application Number
- CN202410176239.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-07
- Publication Date
- 2025-08-08
AI Technical Summary
When the prior art reduces the proportion of adhesive mass in lithium/sodium-based battery electrodes, the bond area is reduced, the peeling force and cohesion force are reduced, the integrity of the conductive network is easily damaged, the impedance increases, and the cycle life is attenuated.
Using latex with core-shell structure as binder, the polymerization reaction of the oil phase and aqueous phase mixture was prepared by shearing the treatment of the oil phase and the aqueous phase mixture at 0.1-1 MPa to prepare the binder polymer particles with a cavity structure for the preparation of the electrode sheet of the electrochemical device.
The high level of bonding force is achieved at a lower latex quality dosage, which improves the energy density and cycle stability of the electrochemical device, and ensures the excellent cycle stability of the battery.
Smart Images

Figure CN120441743A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a latex, a preparation method thereof and an electrochemical device. Background Art
[0002] Improving gravimetric energy density is a key challenge in the development of lithium- and sodium-based batteries. Reducing the mass fraction of binders in lithium- and sodium-based battery electrodes is a simple and effective approach. However, this approach typically reduces the bonding area, leading to decreased peeling and cohesive forces, making the integrity of the conductive network vulnerable to damage. This ultimately manifests as increased impedance and decreased cycle life in lithium- and sodium-based batteries.
[0003] To lower the limit on binder usage, researchers are committed to developing various high-performance binders. Typical approaches include introducing polar functional groups, increasing molecular weight, and optimizing the ratio of monomers. However, these existing strategies have limited potential for improving adhesion and are unable to significantly reduce binder usage. Summary of the Invention
[0004] To address the existing art's inability to reduce the mass fraction of binder in battery pole pieces while simultaneously maintaining battery cycling stability, a latex, a preparation method thereof, and an electrochemical device are provided. The latex provided by the present invention, when used as a binder in the pole pieces of an electrochemical device, can achieve high levels of bonding strength at relatively low latex dosages, thereby achieving a balance between the energy density and cycling stability of the electrochemical device.
[0005] In a first aspect, the present invention provides a latex, which is a dispersion comprising a binder and a solvent; the binder comprises particles having a core-shell structure; wherein the core of the core-shell structure is a cavity; the shell of the core-shell structure is a binding polymer; and the solvent comprises water.
[0006] In a second aspect, the present invention provides a method for preparing the latex as described above, comprising the following steps:
[0007] The mixture of the oil phase and the water phase is sheared, polymerized at a pressure of 0.1-1 MPa, and then the pressure is released to obtain the product;
[0008] Wherein, the oil phase comprises alkanes and the raw materials of the binding polymer; the boiling point of the alkanes is lower than 100° C.; the raw materials of the binding polymer at least comprise monomers;
[0009] The aqueous phase includes water and an emulsifier.
[0010] In a third aspect, the present invention provides an electrochemical device, wherein the latex as described above is used in the preparation process of the electrode.
[0011] On the basis of conforming to the common sense in this field, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0012] The reagents and raw materials used in the present invention are commercially available.
[0013] The positive progress of the present invention is that the latex provided by the present invention can achieve the bonding strength level of the existing binder at a higher mass dosage at a lower mass dosage of latex; when the latex is used as a bonding material for the preparation of electrodes of electrochemical devices (especially lithium / sodium-based batteries), the mass proportion of the binder can be reduced while the electrochemical device has a higher mass energy density and the battery has excellent cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is the SEM image of the latex in Example 1.
[0015] Figure 2 This is the TEM image of the latex in Example 1. DETAILED DESCRIPTION
[0016] The present invention is further illustrated by way of examples below, but the present invention is not limited to the scope of the examples. Experimental methods in the following examples where specific conditions are not specified were performed according to conventional methods and conditions, or selected according to the product specifications.
[0017] latex
[0018] In the latex provided in the first aspect of the present invention, it is a dispersion comprising a binder and a solvent; the binder comprises particles having a core-shell structure; wherein the core of the core-shell structure is a cavity; the shell of the core-shell structure is a binding polymer; and the solvent comprises water.
[0019] In some alternative embodiments, the latex is an aqueous dispersion.
[0020] In the present invention, the true density of the binder can be 0.3-0.95 g / cm 3 , preferably 0.3-0.9g / cm 3 , for example 0.32 g / cm 3 , 0.36g / cm 3 , 0.44g / cm 3 , 0.74g / cm 3 or 0.91g / cm 3 The true density of the binding polymer itself is generally 1.0-1.5 g / cm 3It can be seen that the true density of the binder of the present invention can reflect that most of the binder is a core-shell structure particle with a hollow core rather than a solid particle. The true density of the binder can be tested by conventional testing methods in the field to obtain the mass and volume of the binder, and then calculated according to the calculation formula. The calculation formula of the true density of the binder is: True density = m 粘结剂 / V 粘结剂 , where m 粘结剂 is the mass of the binder, V 粘结剂 is the volume of the binder.
[0021] In the present invention, the porosity of the binder may be no less than 50%. Porosity refers to the ratio of the volume of the cavity in the binder to the total volume of the binder. Ideally, all particles in the binder are particles with a core-shell structure. In this case, taking a single core / single shell calculation as an example:
[0022] P=V 空腔 / V 颗粒
[0023] In the above formula, P refers to the porosity of a single particle (the proportion of the cavity volume), V 空腔 —The volume of the cavity in the particle, V 颗粒 —Total volume of particles.
[0024] In the present invention, the porosity of the binder can be obtained by TEM pictures. 空腔 and V 颗粒 , which can be obtained by substituting it into the above formula.
[0025] In some optional embodiments, the particle size of the binder is 0.1-10 μm, for example, 0.3 μm.
[0026] In some optional embodiments, the shell thickness of the core-shell structure is 0.01-1 μm, optionally 15-50 nm, for example 20 nm, 30 nm, 40 nm or 45 nm.
[0027] In some optional embodiments, the particles having a core-shell structure account for more than 99% by mole of all particles in the binder.
[0028] In some optional embodiments, the solid content of the latex is ≤60%, for example, 9.2%, 9.9% or 16.9%, where the percentage is the mass percentage of the binder in the latex.
[0029] Preparation method of latex
[0030] The second aspect of the present invention provides a method for preparing latex, which includes the following steps: shearing a mixture of an oil phase and an aqueous phase, polymerizing it at a pressure of 0.1-1 MPa, and releasing the pressure to obtain the latex; wherein the oil phase includes alkanes and the raw materials of the binding polymer; the boiling point of the alkanes is lower than 100°C; the raw materials of the binding polymer include at least monomers; and the aqueous phase includes water and an emulsifier.
[0031] When the polymerization reaction pressure is lower than 0.1 MPa, the alkane is easy to escape, which is not conducive to the escape of the alkane during the subsequent pressure release process to form a hollow core-shell structure.
[0032] When the boiling point of the alkane is higher than 100° C., it is difficult for the alkane to escape during the pressure release process, which is not conducive to obtaining a hollow core-shell structure through the escape of the alkane.
[0033] In a preferred embodiment, the boiling point of the alkane is below 80°C.
[0034] In one embodiment, the alkane has a boiling point of 27.5°C.
[0035] In some optional embodiments, the mass ratio of the oil phase to the water phase is 1:(1.5-9), optionally 1:(3.3-6.3), for example, 1:1.7, 1:2.9, 1:3.4, 1:4, 1:8.3, or 1:8.5. The mass ratio of the oil phase to the water phase primarily affects the stability of the latex. Only when the mass ratio of the oil phase to the water phase is within an appropriate range can the resulting latex have better stability.
[0036] In some optional embodiments, the mass ratio of the alkane to the monomer is 1:(0.4-6), for example, 2:1, 1.5:1, 1:2 or 1:5.
[0037] In the present invention, the mass ratio of the emulsifier to water may be (0.01-5):(150-1000), for example, 0.01:1000.
[0038] In the present invention, the shear treatment step can be performed using a strong shear liquid-liquid dispersion device, which preferably includes one of a high-speed shearing machine, a high-pressure homogenizer, a cell crusher and a high-gravity field generating device, such as a high-speed shearing machine or an ultrasonic cell crusher.
[0039] In some optional embodiments, the shearing speed of the high-speed shearing machine is 2000-5000 rpm.
[0040] In some optional embodiments, the power of the ultrasonic cell disruptor is 200-500W.
[0041] In the present invention, the shearing treatment time may be 5-15 minutes.
[0042] In the present invention, the shear treatment temperature may be lower than ambient temperature. The ambient temperature refers to the temperature of the environment during the shear treatment, preferably 25° C. The shear treatment temperature is lower than ambient temperature to prevent the high temperature from causing a large amount of vaporization of low-boiling-point alkanes.
[0043] In the present invention, the polymerization reaction temperature may be 50-85°C, for example 75°C.
[0044] In the present invention, the polymerization reaction time may be 6-12 hours, for example, 10 hours.
[0045] In the present invention, the alkane may include C5-C 10 One or more short-chain alkanes.
[0046] In some embodiments, the alkane is isopentane.
[0047] In some optional embodiments, the monomer includes one or more of acrylate, methacrylate, hydroxyethyl acrylate, styrene, acrylic acid, butadiene, methacrylic acid, acrylonitrile, methacrylonitrile, acrylamide, and derivatives thereof.
[0048] In the present invention, the raw materials of the binder polymer may further include an initiator. The initiator may be an azo initiator and / or a peroxide initiator having a water solubility of less than or equal to 0.5 g / kg water at 25°C. The azo initiator preferably includes azobisisobutyronitrile and / or azobisisoheptanenitrile; the peroxide initiator preferably includes one or more of benzoyl peroxide, ammonium persulfate, and potassium persulfate.
[0049] In some embodiments, the initiator is azobisisobutyronitrile.
[0050] In the present invention, the raw materials of the binding polymer may further include a cross-linking agent. The cross-linking agent may be any conventional cross-linking agent in the art, and may generally include one or more of divinylbenzene, ethylene glycol dimethacrylate, allyl methacrylate, ethylene glycol diacrylate, butylene glycol diacrylate, butylene glycol dimethacrylate, neopentyl glycol dimethacrylate, dimethacrylate adipate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, trimethylolpropane, and pentaerythritol tetramethacrylate.
[0051] In some embodiments, the cross-linking agent is divinylbenzene.
[0052] In some optional embodiments, the emulsifier includes one or more of sodium lauryl sulfate, cetyltrimethylammonium bromide, polyoxyethylene terephthalate, OP surfactants, Span surfactants, Tween surfactants and sodium dodecylbenzene sulfonate.
[0053] In some embodiments, the emulsifier is sodium lauryl sulfate.
[0054] In some optional embodiments, the aqueous phase further comprises one or more of a dispersant, a metal salt, and an inhibitor.
[0055] The dispersant can improve the stability of large-size latex particles. The dispersant can be a conventional dispersant in the art, generally selected from one or more of polyvinyl alcohol, magnesium hydroxide, calcium carbonate, calcium phosphate, silica sol, polyvinyl pyrrolidone, styrene-maleic anhydride copolymer and carboxymethyl cellulose, for example, polyvinyl alcohol.
[0056] The metal salt can reduce the diffusion of highly water-soluble monomers in the aqueous phase, capture free radicals in the aqueous phase, and improve the synthesis efficiency of the core-shell structure. The metal salt can be a conventional metal salt in the art, generally an ionic compound such as sodium chloride.
[0057] The polymerization inhibitor may include one or more of nitrite and potassium dichromate.
[0058] In some optional embodiments, the oil phase includes an initiator, an alkane, a monomer, and a cross-linking agent, wherein the mass ratio of the initiator, the alkane, the monomer, and the cross-linking agent may be (0.5-3): (20-200): 100: (2-10).
[0059] In some optional embodiments, the aqueous phase includes a dispersant, an emulsifier, a metal salt, an inhibitor and water, wherein the mass ratio of the dispersant, emulsifier, metal salt, inhibitor and water may be (1-50): (0.01-5): 1: (0.01-2): (150-1000).
[0060] electrochemical devices
[0061] In the electrochemical device described in the third aspect of the present invention, the latex described above is used in the preparation process of the electrode.
[0062] In the present invention, the electrode sheet is preferably a negative electrode sheet.
[0063] In the present invention, the electrochemical device may be a sodium ion battery or a lithium ion battery, preferably a lithium ion battery.
[0064] In some optional embodiments, the lithium-ion battery includes the negative electrode sheet, the positive electrode sheet, the separator and the electrolyte.
[0065] negative electrode
[0066] In some optional embodiments, the negative electrode sheet can be prepared using conventional methods in the art. For example, the following method can be used: the negative electrode active material, the conductive agent, the latex, and the thickener are mixed in a certain mass ratio, and a solvent is added and mixed uniformly to obtain a negative electrode slurry; the negative electrode slurry is then evenly coated on the negative electrode current collector; and the negative electrode sheet is prepared through drying, rolling, cutting, and other processes.
[0067] The mass ratio of the negative electrode active material, the conductive agent, the latex, and the thickener may be (96.4-98.1):0.5:(0.9-2.6):0.5, wherein the mass ratio is calculated based on the mass of the solid phase in the latex.
[0068] The negative electrode active material may be a negative electrode active material conventionally used in the art for preparing negative electrode sheets, and may be one or more of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microbeads, silicon oxide, and silicon carbon.
[0069] The addition of the thickener can increase the system viscosity of the components in the negative electrode slurry, and the thickener can be a thickener conventionally used in the art for preparing negative electrode sheets, such as sodium carboxymethyl cellulose (CMC).
[0070] The conductive agent is not particularly limited, as long as it is conductive and does not cause chemical changes in the battery. Examples include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black (Super P), acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, or carbon fiber; metal powders or fibers, such as copper, nickel, aluminum, or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives.
[0071] As for the negative electrode current collector, the negative electrode current collector can be a current collector conventionally used for negative electrodes in the art, and can be a common current collector or a composite current collector. The negative electrode current collector can use, without restriction, a material that does not cause chemical changes and has conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, calcined carbon or aluminum-cadmium alloy, or copper, stainless steel or aluminum-cadmium alloy surface-treated with carbon, nickel, titanium or silver can be used. In addition, in order to enhance the adhesion of the negative electrode active material, micro-embossing can be formed on the surface of the negative electrode current collector. The negative electrode current collector can be used in various forms, such as a film, sheet, foil, mesh or porous body.
[0072] In some optional embodiments, the thickness of the negative electrode current collector may be 5-10 μm.
[0073] In some specific embodiments, the negative electrode current collector is a copper foil with a thickness of 10 μm.
[0074] positive electrode
[0075] In some optional embodiments, the positive electrode sheet can be prepared using conventional methods in the art. For example, the following method can be used: after mixing the positive electrode active material, conductive agent, and binder in a certain mass ratio, adding a solvent and mixing uniformly to obtain a positive electrode slurry; then, the positive electrode slurry is evenly coated on the positive electrode current collector; and then, the positive electrode sheet is obtained by drying, cold pressing, and slitting.
[0076] The positive electrode active material is a positive electrode active material conventionally used in the art for preparing positive electrode sheets, such as LiFePO4 or LiNi 0.5 Co 0.2 Mn 0.3 O2 ternary positive electrode material.
[0077] The conductive agent is not particularly limited, as long as it is conductive and does not cause chemical changes in the battery. Examples include: graphite, such as natural graphite or artificial graphite; carbon-based materials, such as carbon black (Super P), acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, or carbon fiber; metal powders or fibers, such as copper, nickel, aluminum, or silver; conductive whiskers, such as zinc oxide whiskers or potassium titanate whiskers; conductive metal oxides, such as titanium dioxide; or conductive polymers, such as polyphenylene derivatives.
[0078] Among them, the binder plays a role in improving the bonding effect between the positive electrode active materials and the adhesion effect between the positive electrode active materials and the positive electrode current collector. The type of the binder is not particularly limited. Specific examples of the binder may include polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinyl pyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber or various copolymers thereof, and any one thereof or a mixture of two or more thereof may be used.
[0079] For the positive electrode current collector, any material that does not cause chemical changes and has high conductivity can be used without restriction. For example, stainless steel, aluminum, nickel, titanium, or calcined carbon, or aluminum or stainless steel that has been surface-treated with carbon, nickel, titanium, silver, or the like, can be commonly used. To enhance the adhesion of the positive electrode active material, micro-embossing can be formed on the surface of the positive electrode current collector. The positive electrode current collector can be used in various forms, such as films, sheets, foils, meshes, or porous bodies.
[0080] In some optional embodiments, the thickness of the positive electrode current collector may be 8-16 μm.
[0081] In some specific embodiments, the positive electrode current collector is an aluminum foil with a thickness of 16 μm.
[0082] diaphragm
[0083] In some optional embodiments, the separator is a polypropylene film or a polyethylene film.
[0084] The air permeability of the diaphragm may be 180-380s / 100mL.
[0085] The porosity of the diaphragm may be 30%-50%.
[0086] The thickness of the separator may be 12 μm.
[0087] In a specific embodiment, the separator is a polypropylene film; the thickness of the separator is 12 μm; the air permeability of the separator is 230 s / 100 mL; and the porosity of the separator is 40%.
[0088] electrolyte
[0089] In some embodiments, the electrolyte may be an electrolyte conventionally used in lithium-ion batteries in the art, generally including a non-aqueous solvent, a lithium salt, and additives.
[0090] The non-aqueous solvent may be a conventional non-aqueous solvent in the art, preferably an ester solvent, more preferably a carbonate solvent. The carbonate solvent may be selected from one or more of ethylene carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).
[0091] Among them, the additive can be selected from one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl ethylene carbonate (VEC), diethylene sulfate (DTD), vinylene sulfate, 1,3-propane sultone (PS), allyl sultone and 1,4-butane sultone.
[0092] The lithium salt may be a conventional lithium salt in the art, such as LiPF6.
[0093] In the present invention, the preparation method of the lithium-ion battery can be a conventional preparation method in the field, which can be a battery cell obtained by winding the positive electrode sheet, the negative electrode sheet and the separator, and then packaging them in a packaging shell and injecting the electrolyte; or it can be a battery cell obtained by stacking the negative electrode sheet, the separator, the positive electrode sheet and the separator in this order, and then packaging them in a packaging shell and injecting the electrolyte.
[0094] On the basis of conforming to the common sense in this field, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0095] Example 1
[0096] Preparation of latex
[0097] (1) 0.5 parts by mass of azobisisobutyronitrile, 200 parts by mass of isopentane, 100 parts by mass of monomers (including 50 parts by mass of styrene, 40 parts by mass of hydroxyethyl acrylate and 10 parts by mass of methyl methacrylate), and 2 parts by mass of divinylbenzene were mixed to form an oil phase.
[0098] (2) 10 parts by mass of polyvinyl alcohol, 0.01 parts by mass of sodium lauryl sulfate, 0.01 parts by mass of sodium nitrite and 1 part by mass of sodium chloride were dispersed or dissolved in 1000 parts by mass of deionized water to form an aqueous phase.
[0099] (3) The oil phase and the aqueous phase were mixed, and the resulting mixture was sheared using a high-speed shearing machine at 5000 rpm for 10 minutes to obtain an oil / water dispersion system, wherein the mass ratio of the oil phase to the aqueous phase was 1:3.3.
[0100] (4) The above oil / water dispersion system was transferred to an autoclave, the pressure in the autoclave was controlled at 0.6 MPa, the temperature was raised to 70°C, and the polymerization was carried out for 8 hours, and the pressure was released to obtain the product.
[0101] The latex obtained in Example 1 was tested using an electron scanning electron microscope (SU-8010, Hitachi, Japan), and the SEM images ( Figure 1 The latex obtained in Example 1 was tested using an electron transmission electron microscope (HT-7700, Hitachi, Japan) to obtain a TEM image (as shown in FIG. Figure 2 ). Figure 2 It can be seen that the latex prepared in Example 1 includes particles having a core-shell structure, wherein the core of the core-shell structure is a cavity. In the above SEM and TEM tests, the sample preparation method is: take 0.01 mL of latex, dilute it 5 to 10 times, and then dry it to obtain latex particles.
[0102] Example 2
[0103] Preparation of latex
[0104] On the basis of Example 1, other conditions were kept unchanged, and only the amount of isopentane in step (1) was changed to 150 parts by mass.
[0105] Example 3
[0106] Preparation of latex
[0107] On the basis of Example 1, other conditions were kept unchanged, and only the amount of divinylbenzene in step (1) was changed to 10 parts by mass.
[0108] Example 4
[0109] Preparation of latex
[0110] On the basis of Example 3, other conditions were kept unchanged, and only the amount of isopentane in step (1) was changed to 50 parts by mass.
[0111] Example 5
[0112] Preparation of latex
[0113] On the basis of Example 1, other conditions were kept unchanged, and only the amount of isopentane in step (1) was changed to 20 parts by mass.
[0114] Example 6
[0115] Preparation of latex
[0116] On the basis of Example 1, other conditions were kept unchanged, and only the amount of isopentane in step (1) was changed to 16.7 parts by mass.
[0117] Example 7
[0118] Preparation of latex
[0119] On the basis of Example 1, other conditions were kept unchanged, and only the amount of isopentane in step (1) was changed to 250 parts by mass.
[0120] Example 8
[0121] Preparation of latex
[0122] On the basis of Example 1, other conditions were kept unchanged, and only the amount of sodium lauryl sulfate in step (2) was changed to 5 parts by mass.
[0123] Example 9
[0124] Preparation of latex
[0125] On the basis of Example 1, other conditions were kept unchanged, and only the amount of sodium lauryl sulfate in step (2) was changed to 6 parts by mass.
[0126] Example 10
[0127] Preparation of latex
[0128] On the basis of Example 1, keeping other conditions unchanged, only the amount of polyvinyl alcohol in step (2) was changed to 5 parts by mass, the amount of sodium lauryl sulfate was 0.005 parts by mass, the amount of sodium nitrite was 0.005 parts by mass, the amount of sodium chloride was 0.5 parts by mass, and the amount of deionized water was 500 parts by mass.
[0129] By adjusting the specific parameters of the above process, latexes with different properties in Examples 1-10 were obtained.
[0130] Comparative Example 1
[0131] The latex used is Japan ZEON BM-451B latex.
[0132] Comparative Example 2
[0133] The latex used is Japan ZEON BM-451B latex.
[0134] The true density, porosity and particle size of the binder in the latex of Examples 1-10, the shell thickness of the core-shell structure and the relationship between the amounts of each component in the latex and the true density, porosity and particle size of the binder in the latex of Comparative Examples 1-2 are listed in Table 1.
[0135] The true density of the binder can be calculated by the following test method: Take a certain volume as V 胶乳 latex, mass m 胶乳 , and then dry it to vaporize the solvent, and the mass of the collected solvent is m 溶剂 , the volume is V 溶剂 The true density of the binder can be calculated by the following formula: True density = m 粘结剂 / V 粘结剂 =(m 胶乳 -m 溶剂 ) / (V 胶乳 -V 溶剂 The specific operation of the true density test method is a conventional technical means in this field and will not be repeated here.
[0136] The porosity of the binder can be predicted by the following calculation method. The specific calculation method is as follows: Taking the single core / single shell calculation as an example:
[0137] P=V 烷烃 =ρ 粘结聚合物 / (ρ 粘结聚合物 +ρ 烷烃 ×m 粘结聚合物 / m 烷烃 )
[0138] In the above formula, P refers to the porosity of a single particle (the proportion of the cavity volume), V 烷烃 —volume fraction of alkanes, ρ 粘结聚合物 —density of the bonding polymer, m 粘结聚合物 —The mass of the monomer, m 烷烃 —The mass of the alkane. The formula assumes: (1) the core-shell structure is complete and symmetrical; (2) the alkane / binding polymer phase separation is complete.
[0139] Table 1
[0140]
[0141] Note: “ / ” in Table 1 indicates that the condition parameters are not involved in the specific experiment.
[0142] Effect Example 1
[0143] (1) Preparation of negative electrode sheet
[0144] The preparation method of the negative electrode sheet adopts the following steps:
[0145] For the negative electrode sheets of Examples 1-10 and Comparative Examples 1-2, the negative electrode active materials graphite, conductive carbon black, latex, and thickener sodium carboxymethyl cellulose (CMC) were mixed according to the amounts specified in Table 2. Deionized water was added as a solvent and stirred until uniformly mixed to produce a negative electrode slurry. The negative electrode slurry was evenly coated onto a 10 μm copper foil current collector. After drying, rolling, and cutting, the negative electrode sheets of Examples 1-10 and Comparative Examples 1-2 were prepared. The rolling pressure was 5 T.
[0146] (2) Peel force test of electrode
[0147] Cut the electrode to be tested into a long strip (length x width = 10 cm x 3 cm) and adhere it to a long quartz glass plate (slightly larger than the electrode) with VHB tape. Repeatedly roll the electrode three times with a dedicated small round roller to ensure sufficient adhesion between the electrode and the VHB. Test the electrode peel force using a universal tensile machine, selecting the standard 180° peel force method. Test each sample three times and take the average value.
[0148] The results of the above tests are listed in Table 2.
[0149] Effect Example 2
[0150] Preparation of lithium-ion batteries
[0151] (1) Preparation of positive electrode sheet: The positive electrode active material lithium iron phosphate, conductive carbon black (Super P), and binder polyvinylidene fluoride (PVDF) were mixed uniformly in a mass ratio of 97:1:2 (a total of 100 parts by mass). N-methylpyrrolidone (NMP) was then added and stirred to uniformly disperse the mixture to obtain a lithium-ion battery positive electrode slurry. The positive electrode slurry was evenly coated on a 16 μm thick aluminum foil. After drying, rolling, and cutting, the positive electrode sheet was obtained.
[0152] Among them, the surface density of the positive electrode is 19.88 mg / cm 2 The size of the positive electrode sheet is cut to 45mm×58mm. The mass of the positive electrode active material is: the surface density of the positive electrode sheet × area × the mass ratio of the positive electrode active material, which is 19.88mg / cm 2 ×45mm×58mm×97%. The positive electrode sheets in each embodiment and comparative example are the same.
[0153] (2) Preparation of negative electrode sheet: The preparation of negative electrode sheet is the same as (1) of Example 1. The size of negative electrode sheet is cut into 50mm×60mm, and the mass of negative electrode active material is: surface density of negative electrode sheet×area×mass ratio of negative electrode active material.
[0154] When the negative electrode sheet was prepared using the latex of Comparative Example 1, the surface density of the negative electrode sheet was 9.0 mg / cm 2 The mass of the negative electrode active materials used in Examples 1-10 and Comparative Example 2 is the same as that in Comparative Example 1.
[0155] When the mass of the negative electrode active material is greater than that of the positive electrode active material, the initial discharge capacity is determined by the amount of the positive electrode active material. When the amount of the positive electrode active material is consistent, the initial discharge capacity should also be consistent. Any difference is only regarded as a measurement error.
[0156] (3) Preparation of electrolyte: Ethylene carbonate (EC) and propylene carbonate (PC) were uniformly mixed in a volume ratio of 1:1, and then an appropriate amount of LiPF6 was dissolved in the above mixed solution to prepare an electrolyte with a concentration of 1 mol / L.
[0157] (4) Preparation of the diaphragm: The diaphragm is a polypropylene film; the thickness of the diaphragm is 12 μm, the air permeability of the diaphragm is 230 s / 100 mL, and the porosity of the diaphragm is 40%.
[0158] (5) Preparation of lithium-ion batteries: The prepared positive electrode sheets, separators, negative electrode sheets made from the latex of Examples 1-10 and Comparative Example 1, and electrolytes were assembled in order (8 layers of positive electrode sheets and 9 layers of negative electrode sheets), and the positive electrode sheets, separators, negative electrode sheets made from the latex of Examples 1-10 and Comparative Example 1, and separators were alternately combined to obtain a soft-pack battery with a capacity of 1 Ah after formation.
[0159] The negative electrode sheets and lithium-ion batteries prepared from the latexes of Examples 1-10 and Comparative Example 1 were tested as follows:
[0160] Test method for capacity retention rate (%) of lithium-ion battery after 1000 cycles:
[0161] At a constant temperature of 25°C, the battery was charged at a constant current and voltage rate of 1C to 4.25V (with a constant voltage cutoff current of 0.05C), followed by a constant current discharge rate of 0.33C to 2.8V. This cycle was repeated 1000 times, and the capacity retention rate was calculated as the ratio of the discharge capacity at the 1000th cycle to the initial discharge capacity. The test results are reported in Table 2.
[0162] The results of the above tests are listed in Table 2.
[0163] Table 2 Electrode peeling force of the latex prepared from Examples 1-10 and Comparative Examples 1-2 and electrochemical performance data of the lithium ion batteries prepared therefrom
[0164]
[0165]
[0166] Note: “ / ” in Table 2 indicates that the condition parameters are not involved in the specific experiment.
[0167] The true density of the binder in the latex prepared in Examples 1-10 of the present invention does not exceed 1 g / cm 3 The particles with core-shell structure account for more than 99% of the total particles in the binder by mole percentage, which can be regarded as 100%; while in Comparative Example 1-2, Japan ZEON BM-451B latex is used, and its true density is 1.1g / cm 3 , which are solid particles.
[0168] When preparing negative electrode sheets using the latex of Examples 1-10 of the present invention, the mass amount of latex used was 0.9%-2.6%, while the mass amount of latex used in Comparative Example 1 was 3%. The peeling force of the electrode sheets prepared using the latex of Examples 1-10 of the present invention was comparable to that of the electrode sheet prepared in Comparative Example 1. A comparison of Comparative Examples 1 and 2 shows that the existing Japanese ZEON BM-451B latex must account for at least 3% to function properly. When the latex accounts for less than 3% (e.g., the latex accounts for 2.6% in Comparative Example 2), material shedding occurs and the negative electrode sheet cannot be used.
[0169] When the latexes of Examples 1-10 were used to prepare negative electrode sheets, the capacity retention rate of the resulting lithium-ion batteries (after 1000 cycles) reached 90% or higher, even reaching 91%, when the mass dosage of the latex was 0.9%-2.6%. However, when the mass dosage of the latex used in Comparative Example 1 was 3%, the capacity retention rate of the resulting lithium-ion battery (after 1000 cycles) was 90.4%. This shows that the capacity retention rate of the lithium-ion batteries of the present invention was comparable, even though the amount of latex used was less. In addition, when the latexes of Examples 1-10 were used to prepare negative electrode sheets, the initial discharge capacity and 1000-cycle discharge capacity of the resulting lithium-ion batteries were comparable to those of Comparative Example 1.
[0170] Compared with other examples, the porosity of the binder in the latex obtained in Example 5 and Example 6 is lower, so when used to prepare negative electrode sheets, the required mass amount of latex is higher.
[0171] From the above, it can be seen that the latex of the present invention can achieve the bonding strength level of the existing binder at a higher mass dosage at a lower mass dosage of latex. When the latex is used as a bonding material for the preparation of lithium-ion battery electrodes, the mass proportion of the binder can be reduced while the lithium-ion battery has a considerable energy density, while ensuring that the battery has excellent cycle stability and the cycle life does not decay during use.
[0172] Although specific embodiments of the present invention have been described above, those skilled in the art will appreciate that these are merely illustrative and that the scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, and such changes and modifications are intended to fall within the scope of the present invention.
Claims
1. A latex, characterized in that The invention is a dispersion liquid comprising a binder and a solvent; the binder comprises particles with a core-shell structure; wherein the core of the core-shell structure is a cavity; the shell of the core-shell structure is a binding polymer; and the solvent comprises water.
2. The latex according to claim 1, wherein It satisfies one or more of the following conditions (a)-(c): (a) The true density of the binder is 0.3-0.95 g / cm 3 ; (b) the porosity of the binder is not less than 50%; (c) The particle size of the binder is 0.1-10 μm.
3. The latex according to claim 1, wherein It satisfies one or both of the following conditions (a)-(c): (a) the shell thickness of the core-shell structure is 0.01-1 μm; (b) the core-shell structure comprises one or more of single-core, multi-core, single-shell and multi-shell; (c) The particles having a core-shell structure account for more than 99% by mole of all particles in the binder.
4. The latex according to claim 1, wherein The solid content of the latex is ≤60%, where the percentage is the mass percentage of the binder to the latex.
5. A method for preparing the latex according to any one of claims 1 to 4, characterized in that: It includes the following steps: The mixture of the oil phase and the water phase is sheared, polymerized at a pressure of 0.1-1 MPa, and then the pressure is released to obtain the product; Wherein, the oil phase comprises alkanes and the raw materials of the binding polymer; the boiling point of the alkanes is lower than 100° C.; the raw materials of the binding polymer at least comprise monomers; The aqueous phase includes water and an emulsifier.
6. The method for preparing latex according to claim 5, wherein It satisfies one or more of the following conditions (a)-(h): (a) the boiling point of the alkane is lower than 80°C; (b) the mass ratio of the oil phase to the water phase is 1:(1.5-9); (c) the mass ratio of the alkane to the monomer is 1:(0.4-6); (d) the mass ratio of the emulsifier to water is (0.01-5):(150-1000); (e) the shearing treatment time is 5-15 min; (f) the shearing treatment is performed at a temperature lower than ambient temperature; (g) the polymerization reaction temperature is 50-85° C.; (h) The polymerization reaction time is 6-12h.
7. The method for preparing latex according to claim 5, wherein The preparation method satisfies one or more of the following conditions (a)-(d): (a) The alkanes include C5-C 10 One or more short-chain alkanes; (b) the monomers include one or more of acrylate, methacrylate, hydroxyethyl acrylate, styrene, acrylic acid, butadiene, methacrylic acid, acrylonitrile, methacrylonitrile, acrylamide and derivatives thereof; (c) the raw material of the binding polymer further comprises an initiator; the initiator is selected from azo initiators and peroxide initiators; (d) The raw materials of the binding polymer further include a cross-linking agent; the cross-linking agent includes one or more of divinylbenzene, ethylene glycol dimethacrylate, allyl methacrylate, ethylene glycol diacrylate, butylene glycol diacrylate, butylene glycol dimethacrylate, neopentyl glycol dimethacrylate, dimethacrylate adipate, triethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, trimethylolpropane and pentaerythritol tetramethacrylate.
8. The method for preparing latex according to claim 5, wherein It satisfies one or both of the following conditions (a)-(b): (a) the emulsifier comprises one or more of sodium lauryl sulfate, cetyltrimethylammonium bromide, polyoxyethylene terephthalate, OP surfactant, Span surfactant, Tween surfactant and sodium dodecylbenzene sulfonate; (b) the aqueous phase further comprises one or more of a dispersant, a metal salt and an inhibitor; the dispersant comprises one or more of polyvinyl alcohol, magnesium hydroxide, calcium carbonate, calcium phosphate, silica sol, polyvinyl pyrrolidone, styrene-maleic anhydride copolymer and carboxymethyl cellulose; the metal salt is an ionic compound; and the inhibitor comprises one or more of nitrite and potassium dichromate.
9. The method for preparing latex according to claim 5, wherein The preparation method satisfies one or both of the following conditions (a)-(b): (a) the oil phase comprises an initiator, an alkane, a monomer, and a cross-linking agent, wherein the mass ratio of the initiator, the alkane, the monomer, and the cross-linking agent is (0.5-3): (20-200): 100: (2-10); (b) The aqueous phase comprises a dispersant, an emulsifier, a metal salt, an inhibitor and water, wherein the mass ratio of the dispersant, the emulsifier, the metal salt, the inhibitor and the water is (1-50): (0.01-5): 1: (0.01-2): (150-1000).
10. An electrochemical device, characterized in that The latex according to any one of claims 1 to 4 is used in the preparation process of the electrode.
Citation Information
Cited By
Negative plate, preparation method thereof and solid-state battery
CN121416409A